0124 Sleep, Meal Timing And Motivations For Eating In Australian Flight Attendants. (27th April 2018) - Perrin, S L; Dorrian, J; Coates, A M; Gupta, C C; Centofanti, S A; Beyne, K; Marx, L; Banks, S
Abstract: Introduction: Flight attendants' work unusual schedules, travelling over multiple time zones, in confined and controlled spaces. Specific health issues in flight attendants include chronic circadian misalignment and gastrointestinal disease. This study examined flight attendants sleep and meal timing and how their unique working environment impacted eating patterns and behaviors. Methods: N=31 Australian flight attendants (8 males, BMI 26.1 ± 3.9, 23 females, BMI 25.0 ± 4.9; age range 22–61 years) were asked to recall a typical shift and complete an online sleep and meal/snack timing questionnaire that also included questions about motivations for why, what and when they ate while at work. Two-way, between-subjects ANOVAs were conducted to assess differences in sleep duration between days on and days off. Results: Flight attendants average length of duty was 11.1 ± 3.1h and length of flight was 8.8 ± 3.8h. A main effect of sleep duration between days on ( M =5.19h, SD= 1.57h) and days off ( M =7.63h, SD =1.19h), F (1, 29)=68.1, p=< 0.001) was found. Work and schedule factors changed temporal patterns of eating behavior, with an increase in snacking and a decrease in meals across a typical shift. The highest frequency of food intake was within the first-hour on-shift, with 48% of flight attendants snacking. What, when and why food was consumed, was largely dictated by working time factors, with 73% of flight attendants reporting time available, 57% food available and 49% scheduled work breaks as the primary motivations for eating. Conclusion: Diurnal sleeping and eating patterns change with flight attendants' work patterns. What, why and when flight attendants ate while at work was primarily determined by the timing of breaks and other work constraints. Irregular eating behaviors have potential health consequences and may be a mechanism by which chronic disease is increased in this population. Altering when workers eat may be a potential intervention to reduce the impact of chronic disease. Interventions to improve flight attendant diet and health should consider the work environment as a primary driver for eating behavior. Both individual and operation-level approaches are likely to be required. Support (If Any): NA